Internet addiction and aggressiveness in Peruvian high school students - Estrada Araoz, Edwin Gustavo (2020)
In recent years the internet has positioned itself as a useful, functional and necessary tool for students to develop mainly their academic and social activities. However, it’s inappropriate and excessive use could cause physical and psychological problems in students, affecting their quality of life. For this reason, the present research aimed to determine the relationship between internet addiction and aggressiveness in students at the secondary education level of a public educational institution in Madre de Dios, Peru. The research had a quantitative approach, an experimental design and was correlational. The sample consisted of 170 students to whom the Lima Internet Addiction Scale and the Aggression Questionnaire were applied, instruments with adequate levels of validity and reliability. According to the results, the students were characterized by moderate levels of internet addiction, average levels of aggressiveness and it was determined that the correlation coefficient between both variables was 0.643 with a p-value lower than the significance level (p<0.05). It was concluded that there is a direct and statistically significant relationship between internet addiction and aggressiveness.